Mantle lithosphere control of crustal tectonics and magmatism of the western Ohre (Eger) Rift - Babuska,V.; Plomerova,J. (Journal of Geosciences, 2010)
This paper summarizes our recent research on the relationship between tectonics of the mantle lithosphere and of the upper crust in the western Bohemian Massif (BM). The rejuvenated Variscan junction of three mantle domains, the Saxothuringian (ST), Moldanubian (MD) and Tepla-Barrandian (TB), delimited by different orientation of seismic anisotropy reflecting a consistent fossil olivine orientation and belonging to originally separated microplates, plays important role in the crustal architecture of the region. The crust above the mantle junction is the most active part of the BM characterized by periodic earthquake swarms and mofettes emitting gases of mantle origin. Detected offsets of surface boundaries of the three units from their mantle counterparts indicate a detachment of the rigid upper crust from the mantle lithosphere. Locations of major tectonic features like the Ohre (Eger) Rift, the West Bohemian Shear Zone and the Marianske Lazne Fault were probably predisposed by the boundaries of the mantle lithosphere domains. We have suggested that the sublithospheric mantle of the western BM acted as a major provider for heat and partial melts and the Variscan mantle boundaries served as magma conduits for the late-orogenic granitic magmatism and after their rejuvenation, also for the Cenozoic volcanism. Similarly, the boundaries may have pre-conditioned the subsequent locations of sedimentary basins. It is possible that also in other regions some of these so called intra-plate phenomena can be related to partly healed up and later rejuvenated microplate boundaries.
Keywords: mantle lithosphere domains; seismic anisotropy; Ohre (Eger) Rift; mantle sutures; control of crust architecture